2014
DOI: 10.4018/ijegr.2014040102
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Intention Towards E-Government in Malaysia

Abstract: This study examines an amplified unified theory of acceptance and use of technology (UTAUT) in the context of eGovernment to get a better understanding of users' behaviour towards eGovernment. Two hundred and six respondents (206) participated in the study and the data was analysed using structural equation modelling (SEM). The study revealed that Performance Expectancy, Risk Taking Propensity, Attitude towards Computer and Web Trust dimensions are essential precursor of behavioural intention of Malaysians tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Wherever possible, this study’s variables were measured using multiple-item measures that have been successfully tested in earlier studies. When dealing with research models including latent variables and their complex interrelations, structural equation modelling has been determined as a superior statistical method (Hair, 2017), and is particularly suitable in the public administration context (Taiwo et al., 2014). Since this study has a mainly confirmatory, hypothesis-testing character, covariance-based structural analysis has been applied (Hair et al., 2014).…”
Section: Methods and Datamentioning
confidence: 99%
“…Wherever possible, this study’s variables were measured using multiple-item measures that have been successfully tested in earlier studies. When dealing with research models including latent variables and their complex interrelations, structural equation modelling has been determined as a superior statistical method (Hair, 2017), and is particularly suitable in the public administration context (Taiwo et al., 2014). Since this study has a mainly confirmatory, hypothesis-testing character, covariance-based structural analysis has been applied (Hair et al., 2014).…”
Section: Methods and Datamentioning
confidence: 99%
“…Still, they failed to address the critical user privacy issues. Several different studies in the past have attempted to partially address the issue by incorporating security (Albugami and Bellaaj, 2014;Moraes and Meirelles, 2017;Moryson and Moeser, 2016;Nelloh et al, 2019), risk (Clark et al, 2019;Hansen et al, 2018;Kim et al, 2008;Kim and Lennon, 2013;Taiwo et al, 2014) and Tr (Chao, 2019;Hansen et al, 2018;Kabra et al, 2017;Kim et al, 2008;Moraes and Meirelles, 2017;Moryson and Moeser, 2016;Taiwo et al, 2014) to better predict BIU, but have never explored the relationships between these constructs simultaneously.…”
Section: Research Implicationsmentioning
confidence: 99%
“…However, this particular significant factor has not been explored much more in the context of e-government (Srivastava and Teo 2009 ; Karunasena and Deng 2009 ; Alaaraj and Ibrahim 2014 ) further, it is noted that the importance of trust in an online business environment has been explored tremendously (Lee et al 2015 ), but it is few in the context of e-government. Accordingly, trustworthiness plays a crucial role for acceptance, adoption and use of e-government services in a country (Rufin et al 2014 ; Taiwo et al 2014 ). According to the investigation done by Rana et al ( 2015b ) titled A meta-analysis of existing research on citizen adoption of e-government, it was revealed that no proper study has done in the context of Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%